Extracellular Vesicles: Packages Sent With Complement - Karasu, Ebru; Eisenhardt, Steffen U.; Harant, Julia; Huber-Lang, Markus (Frontiers in Immunology, 2018)
Cells communicate with other cells in their microenvironment by transferring lipids, peptides, RNA and sugars in extracellular vesicles (EVs), thereby also influencing recipient cell functions. Several studies indicate, that these vesicles are involved in a variety of critical cellular processes including immune, metabolic and coagulatory responses, and are thereby associated with several inflammatory diseases. Furthermore, EVs also possess anti-inflammatory properties and contribute to immune regulation, thus encouraging an emerging interest in investigating and clarifying mechanistic links between EVs and innate immunity. Current studies indicate complex interactions of the complement system with EVs, with a dramatic influence on local and systemic inflammation. During inflammatory conditions with highly activated complement, including after severe tissue trauma and during sepsis, elevated numbers of EVs were found in the circulation of patients. There is increasing evidence that these shed vesicles contain key complement factors as well as complement regulators on their surface, affecting inflammation and the course of disease. Taken together, interaction of EVs regulates complement activity and contribute to the pro- and anti-inflammatory immune balance. However, the molecular mechanisms behind this interaction remain elusive and require further investigation. The aim of this review is to summarize the limited current knowledge on the crosstalk between complement and EVs. A further aspect is the clinical relevance of EVs with an emphasis on their capacity as potential therapeutic vehicles in the field of translational medicine.